The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/jacs.9b11045
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Correlation: Engineering High Quantum Yields in Down-Shifting Nanophosphors

Abstract: Lanthanides are routinely incorporated into quantum dots to act as down-shifting and up-converting phosphors in display and lighting applications due to their high photoluminescence quantum yields (PLQY). Recent efforts in the field have demonstrated that trivalent lanthanide, Ln­(III), incorporated into ZnAl2O4 spinel nanocrystals can achieve PLQYs of 50% for down-shifting nanophosphors using earth abundant materials. The high PLQY is surprising as the Al­(III) site in a spinel is centrosymmetric, which shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…The ratio, R/O, of the intensities of the red 5 D 0 → 7 F 2 and orange 5 D 0 → F 1 transitions of Eu III can be used to gain insights into the local symmetry of the Eu III ions in the films. 50 This is because the 5 D 0 → 7 F 2 is a hypersensitive transition and can be altered by the Eu III environment. The analysis of Eu(DPA) 3 -containing films revealed that the Eu III ions remained coordinated to the DPA ligands as the R/O values for the metal complexes (3.8), PDADMA/PSS (3.6), and F-P4VP/Nafion (3.7) luminescent films were similar.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio, R/O, of the intensities of the red 5 D 0 → 7 F 2 and orange 5 D 0 → F 1 transitions of Eu III can be used to gain insights into the local symmetry of the Eu III ions in the films. 50 This is because the 5 D 0 → 7 F 2 is a hypersensitive transition and can be altered by the Eu III environment. The analysis of Eu(DPA) 3 -containing films revealed that the Eu III ions remained coordinated to the DPA ligands as the R/O values for the metal complexes (3.8), PDADMA/PSS (3.6), and F-P4VP/Nafion (3.7) luminescent films were similar.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Incorporation of the [Eu­(DPA) 3 ] 3– complexes into the films did not show any significant effect on the color purity of the Eu III emission as the linewidths fwhm of the 5 D 0 → 7 F 2 were determined to be minimally broadened from 2.2(±0.1) to 2.4 nm when incorporated into the F-P4VP/Nafion and PDADMA/PSS films. The ratio, R/O, of the intensities of the red 5 D 0 → 7 F 2 and orange 5 D 0 → 7 F 1 transitions of Eu III can be used to gain insights into the local symmetry of the Eu III ions in the films . This is because the 5 D 0 → 7 F 2 is a hypersensitive transition and can be altered by the Eu III environment.…”
Section: Resultsmentioning
confidence: 99%
“…These inferences are important for designing the phosphor for next-generation LEDs. For an efficient phosphor, it is necessary that phosphors have a strong absorption for light emitted by LED chips. Currently, the most used strategy for the design of new phosphors is based on a trial–error approach which often results in huge consumption of money and time. Thus, by judicially tailoring the first and second coordination shell around the Eu 3+ ion in a mixed oxide, one can design a phosphor aligned with deep and near-UV LED in a rational manner.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal size ( D ) and lattice strain (ε) of the as-obtained samples were estimated by Williamson–Hall (W–H) formula where the term β hkl is the full width at half-maximum (FWHM) of the selected diffraction peak, K is the shape factor (normally 0.9 for spherical nanoparticles), λ represents the wavelength of the X-ray, D is the crystal size, and ε is the strain. Using the (101), (200), (204), and (116) reflections from XRD patterns, D and ε values were evaluated.…”
Section: Results and Discussionmentioning
confidence: 99%